A checklist of the bees (Hymenoptera: Apoidea) of Manitoba, Canada. (27th January 2023) - Gibbs, Jason; Hanuschuk, Emily; Miller, Reid; Dubois, Melanie; Martini, Massimo; Robinson, Steve; Nakagawa, Phoenix; Sheffield, Cory S.; Cardinal, Sophie; Onuferko, Thomas M.
Abstract: We record 392 species or morphospecies of bees (Hymenoptera: Apoidea) for Manitoba, Canada, which is 154 more species than reported in 2015 and includes five new generic records since 2015 ( Ashmeadiella, Brachymelecta, Eucera, Neolarra, and Triepeolus ). Thirteen new records reported here are new for Canada: Calliopsis ( Nomadopsis ) australior Cockerell, Perdita ( Perdita ) tridentata Stevens, Brachymelecta interrupta (Cresson), Diadasia ( Dasiapis ) ochracea (Cockerell), Melissodes bidentis Cockerell, Nomada crawfordi crawfordi Cockerell, Nomada fuscicincta Swenk, Nomada sphaerogaster Cockerell, Nomada xantholepis Cockerell, Triepeolus cf. grindeliae Cockerell, Dianthidium ( Dianthidium ) parvum (Cresson), Coelioxys ( Xerocoelioxys ) nodis Baker, and Megachile ( Megachiloides ) dakotensis Mitchell. We remove the following species from the list of Manitoba bees based on re-examination of voucher material: Andrena ( Ptilandrena ) geranii Robertson, Andrena ( Rhacandrena ) robertsonii Dalla Torre, Andrena ( Simandrena ) nasonii Robertson, Andrena ( Trachandrena ) ceanothi Viereck, Andrena ( Trachandrena ) quintilis Robertson, Lasioglossum ( Hemihalictus ) pectoraloides (Cockerell), Lasioglossum ( Lasioglossum ) forbesii (Robertson), and Dianthidium ( Dianthidium ) concinnum (Cresson). We propose that Nomada alpha paralpha Cockerell, 1921 and N. alpha dialpha Cockerell, 1921 are junior synonyms of N. alpha Cockerell, 1905. Nomada arenicola Swenk, 1912 is considered a junior synonym of N. fervida Smith, 1854. Protandrena albertensis (Cockerell) and Neolarra mallochi Michener are recognised as valid species. We provide additional notes on taxonomy, nomenclature, and behaviour for select species in the list.